(untitled) (Raparin Journal of Humanities (RJH), 2024)
In this study, we show the impact of climate on the rate of consumption of water for production of rice as an agricultural product in Sulaymaniyah governorate, Various data was obtained from multiple weather stations including (Dukan, Chwarta, Penjween, Bazian, Sulaymaniyah and Darbandikhan) from the year 2003until 2016, and also determing those climate factors that have positive and negative influences on the consumption use of water .Thorinthweet equation was used to estimate the amount of potential evapotranspiration using rice plant coefficient.In this investigation, we depend on Description method to describe the relationship between climate elements and consumption of water, with Comparing method to compare consumption of water between the metrological stations, and Depending on this mathematical formula, the amount of water consumption in the study area was also found. Furthermore, effects of geographical distribution at both seasonal and periodic levels of rice crop growth were identified. Our aim in this investigation is the ability to irrigate our crops in a scientific way. Detailed statistical analysis revealed that climatic factors exert great influences of almost 99%, The temperature may come in the first degree for the positive reasons, and for the moisture component in the first degree for the negative reasons.